Integrating Home-Based Exercise Training with a Hospital at Home Service for Patients Hospitalised with Acute Exacerbations of COPD: Developing the Model Using Accelerated Experience-Based Co-Design - Barker, Ruth E (Int J Chron Obstruct Pulmon Dis, 2021)
BACKGROUND: Hospital at home (HaH) schemes allow early discharge of patients hospitalised with an acute exacerbation of chronic obstructive pulmonary disease (AECOPD). Traditional outpatient pulmonary rehabilitation (PR) following an AECOPD has an established evidence-base, but there are issues with low referral, uptake and completion. One commonly cited barrier to PR post-hospitalisation relates to poor accessibility. To address this, the aim of this project was to enrol service users (patients with COPD and informal carers) and healthcare professionals to co-design a model of care that integrates home-based exercise training within a HaH scheme for patients discharged from hospital following AECOPD. METHODS: This accelerated experience-based co-design project included three audio-recorded stakeholder feedback events, using key “touchpoints” from previous qualitative interviews and a recent systematic review. Audio-recordings were inductively analysed using directed content analysis. An integrated model of care was then developed and finalised through two co-design groups, with the decision-making process facilitated by the tables of changes approach. RESULTS: Seven patients with COPD, two informal carers and nine healthcare professionals (from an existing outpatient PR service and HaH scheme) participated in the stakeholder feedback events. Four key themes were identified: 1) individualisation, 2) progression and transition, 3) continuity between services, and 4) communication between stakeholders. Two patients with COPD, one informal carer and three healthcare professionals participated in the first joint co-design group, with five healthcare professionals attending a second co-design group. These achieved a consensus on the integrated model of care. The agreed model comprised face-to-face supervised, individually tailored home-based exercise training one to three times a week, delivered during HaH scheme visits where possible by a healthcare professional competent to provide both home-based exercise training and usual HaH care. CONCLUSION: An integrated model of care has been co-designed by patients with COPD, informal carers and healthcare professionals to address low uptake and completion of PR following AECOPD. The co-designed model of care has now been integrated within a well-established HaH scheme.